The European welfare state regimes: questioning the typology during the crisis - Josifidis, Kosta; Hall, John B.; Supic, Novica; Beker Pucar, Emilija (Technological and Economic Development of Economy, 2015)
This paper examines the nature of changes within the EU–15 welfare states affected by the 2008 crisis. We try to answer the question of whether the differences that exist among different welfare state regimes, according to prevailing welfare state typologies, lead to different responses to the consequences of the crisis. Welfare state regimes are the result of different institutional perceptions of social risks hence it is realistic to expect specific responses to the effects of crisis among different welfare state regimes, and similar responses among the countries that belong to the same welfare state regimes. In order to recognize convergent vs. divergent processes, we perform a comparative analysis of the dynamics of the key welfare state determinants of the EU–15 countries, grouping according to welfare state regimes, in the pre-crisis and crisis periods. The results indicate that institutional rigidity and inherent inertia has remained a key factor of convergent welfare state processes in countries that belong to the Social Democratic and Corporatist welfare state regimes. Deviations from such a course are the most evident in the Mediterranean welfare state regimes, especially in Greece and Portugal where austerity measures have been formulated under the strong influence of the Troika.